The Effect of Kinesio Taping on Pain and Physical Activity in Adolescent with Primary Dysmenorrhea - Arianeputri, Gemma Nurulfatiha; Wahyuni, Wahyuni (FISIO MU: Physiotherapy Evidences, 2024)
Introduction: Dysmenorrhea is a painful cramp that occurs during menstruation and is a common cause of pelvic pain and menstrual disorders. Symptoms of dysmenorrhea last for 24-48 hours which can interfere with physical activity. Kinesio taping administration is done as one way to reduce the level of dysmenorrhea pain in adolescents. The aim was to determine the effect of kinesio taping on pain and physical activity in adolescents with primary dysmenorrhea. Methods: Quasi-experimental with pre-test post-test control group design. The study was conducted at SMAS IT Tariq bin Ziyad, Bekasi, West Java in May. A total of 8 participants are included in this study. The independent variable is Kinesio taping. The dependent variable is pain and physical activity dysmenorrhea. Physical activity using questionnaires of physical activity level (PAL) and visual analogue scale (VAS) to measure the degree of pain dysmenorrhea. Data analysis using Wilcoxon Signed Ranks test and Whitney difference test. Result: Results after administration of KT in the control group, Wilcoxon Signed Ranks test VAS (p=0.109)PAL (p=0.068) and Maan Whitney test VAS (Mean=4.75; p=0.767) and PAL (Mean=6.00; p=0.083). Conclusion: Kinesio taping can influence the pain of primary dysmenorrhea by reducing the level of pain felt and can improve physical activity and quality of life in adolescents with primary dysmenorrhea.